The Extent of Awareness and Application of the Structured Play Strategy by Specialists Working with Children with Autism Spectrum Disorder - Almutlaq, Hajar; Alshiha, Maha (Journal of Ecohumanism, 2025)
This study highlights the critical role of structured play in enhancing the development of children with Autism Spectrum Disorder (ASD) and underscores the necessity of equipping specialists with effective strategies for implementation. Understanding and applying structured play not only improve children's social and cognitive skills but also contribute to the advancement of specialized education and intervention programs.This study aimed to assess the level of awareness and application of the Structured Play Strategy among specialists working with children with ASD in daycare centers within the Riyadh region. The study sample consisted of 219 specialists, including 26 males and 193 females, who work with children with ASD in these centers. To achieve the study's objectives, the researchers employed a descriptive research method. The results indicated that the specialists' awareness of the structured play strategy was high, with 86% demonstrating familiarity with the approach, a finding consistent with previous research. Additionally, the professionals' application of the strategy was also high, with an application rate of 84%. However, the study identified several obstacles that may hinder the effective implementation of the structured play strategy, including the lack of a stimulating environment and difficulties in managing large groups of children. Furthermore, no statistically significant differences were found in the application of the strategy based on variables such as gender, years of experience, or educational qualifications. The study concludes with recommendations for future research.